Memahami Sila Persatuan dalam Konteks Keberagaman di Indonesia - Talita Sembiring; Yakobus Ndona (Asosiasi Ilmuwan Pendidikan, Sosial, dan Humaniora Indonesia, 2024)
This research entitled Understanding the Precept of Unity in the Context of Diversity in Indonesia examines the understanding and implementation of the third precept of Pancasila, namely “Indonesian Unity,” in the context of diversity in Indonesia. This precept emphasizes the importance of national unity amidst the diversity of ethnicity, religion, race, and class. This research uses the library research method by collecting data by understanding and examining theories obtained from various literatures related to the research. The results of this study emphasize that the precepts of Indonesian Unity invite to appreciate and accept differences as the wealth of the nation, not as a threat, with the aim of realizing a peaceful, just and prosperous Indonesia.